Wind–pellet shear sailing. (August 2022) - Greason, Jeffrey K.; Yakymenko, Dmytro; Larrouturou, Mathias N.; Higgins, Andrew J.
Abstract: A propulsion concept in which a spacecraft interacts with both a stream of high-velocity macroscopic pellets and the mass of the interplanetary or interstellar medium is proposed. Unlike previous pellet-stream propulsion concepts, the pellets are slower than the spacecraft and are accelerated backwards as they are overtaken by it, imparting a forward acceleration on the spacecraft. This maneuver is possible due to the interaction with a fixed medium (e.g., interstellar medium); as the spacecraft travels through the medium, it is able to extract power from the relative wind blowing over the spacecraft. As viewed from the rest frame, the kinetic energy of the pellets is transferred to the spacecraft; the source of energy for the propulsive maneuver (i.e., whether the source is the pellets or the wind) is thus reference-frame dependent. This concept relies upon the relative velocities (or shear) between the pellet stream and the fixed medium in order to concentrate the energy of the pellets into the spacecraft and is therefore termed wind–pellet shear sailing. The equations governing the mass ratio of pellets to the spacecraft and its dependence on the final spacecraft velocity are derived, analogous to the classical rocket equation; the critical role of the efficiency of the power extraction and transfer process is identified. Natural sources of energy (photon and particle fluxes from the sun) are considered as a means to accelerate the pellets, produced from in-situ sources of material in the solar system, to velocities of 1000 to 6000 km/s. Techniques for onboard generation of power via electromagnetic interaction with the interstellar medium (ISM) are reviewed, with a repetitively stroked plasma magnet being identified as a promising approach. The necessity of the spacecraft to detect and track the pellets as they are overtaken dictates the desired properties of the pellets. Pellet pushers (i.e., accelerators) on board the spacecraft are also preliminarily explored in their engineering considerations, with electric field accelerators of charged nanometric particles, Lorentz-force accelerated ionized pellets, or expansion of vaporized pellets via a nozzle being highlighted as potential approaches. A preliminary mission profile is defined in which a 500-kg scientific payload is delivered to orbit about α -Centauri, using wind–pellet shear sailing as the intermediate stage to bring the spacecraft from 2% to 5.5% of c, with a total mission duration (launch to arrival) of 27 years. The concept design illustrates the potential for synergy at the low-velocity end with advanced solar photon or solar-wind sailing and at the high-velocity end with the q -drive concept. Highlights: A new concept is proposed: a spacecraft overtakes pellets, transferring their energy to the spacecraft. The concept exploits the use of free energy sources available in space. Analysis suggests spacecraft may be accelerated from 2% to 5% of the speed of light. The technique may be combined with other propulsion devices to achieve greater speeds. A mission to return data from nearby stars within 30 years of launch may be possible.